Dijital İmaj: “Kendi”nin Simulasyonu mu Olmayana Ergi mi? - Güngör, Zeynep (The Turkish Online Journal of Design Art and Communication, 2012)
Apparel is the primary material that a person consulted while creating and identity which is not only who actually he is, but also who he wants to be. In his social life or working life, people dress for impressing others because of mmany effective reasons, or pretending someone else or just to get what he wants. Thus he tells something about himself and over these images the society relates the look with his life-style. Basically, fashion refreshes itself for this deceptions. Human being is able to cover himself in any surroundings even he is most visible in. So, he is influenced by what, in a virtual world where is the most available atmosphere to hide “self”? While he is creating his digital identity called avatar, does he follow his own example or draws a sample of the simulation of a person he wants to be? In this case, it’s studied that; what criterions the gamers take in their costume and image selections during the creation of their visual characters and also this consciousness or underconsciousness is being understood by other gamers in the digital games like The Sims, The Sims Social, Second Life by questing the gamers in several ages, occupations and genders. Finally, it’s been highlighted the importance of apparel in the process of creating a digital ID.
Keywords: Simulation; Digital image; Apparel; Avatar; Simulasyon; Dijital Görsel; Görünüm